Hadith #2666 - Sahih al-Bukhari - Abu 'Abdur-Rahman (Sahih al-Bukhari)
When ‘Uthman (ra) was circled (by the rebels), he looked upon them from above and said, “Ias you by Allah, I ask nobody but the Companions of the Prophet (ﷺ), dont you know that Allah’s Messenger (ﷺ) said, ‘Whoever will (buy and) dig the well of Ruma will be granted Paradise,’ and I (bought and) dug it? Don’t you know that he said. ‘Whoever equip the army of ‘Usra (i.e., Tabuk’s Ghazwa) will be granted Paradise,’ and I equipped it ?” They attested whatever he said. When
Grade: Sahih

Hadith #4739 - Sahih al-Bukhari - Abu 'Abdur-Rahman (Sahih al-Bukhari)
`Ali said, “We were sitting with the Prophet,” (He then mentioned the Hadith above (469).
Grade: Sahih